Detecting the Aspergillus spp. In(BAL) Fluid Samples by Nested PCR, Culture and Direct Smear - Seyed Amir Yazdanparast; Ghazaleh Ghandchi; Fariba Heshmati; Sanam Afshar Moghaddam; Mohammad Ali Khodadoust (Tehran University of Medical Sciences, 2011)
Background and Aim: Aspergillosis are the most prevalent cause of the respiratory infections. These fungi show invasive aspergillosis(IA) in immunocompromised patients. The number of immunocompromised patients are increasing due to immunodisorder illnesses, grafts and immunosuppressor drugs, so, rapid identification methods are very important. The aim of this study was to detect the Aspergillus spp. In fluid samples by nested PCR, and compare with culture and direct smear. Materials and Methods: Conventional detection methods such as culture and direct smear are unsensitive and time consuming. Some methods such as immunodetecting methods have high false positive and are unreliable. Nowadays, molecular methos and PCR are very helpful. These methods are both sensitive and reliable and very rapid. In this study, we used Nested PCR, culture and direct smear to detect Aspergillus spp in BAL fluid samples. Results: This research is a descriptive-comparative study and has been done for rapid identification of fungi related to Aspergillosis such as culture, direct smear and nested- PCR. Findings of this study show that positive results by nested-PCR were more effective and sensitive than culture and direct smear.Conclusions: We found that positive results by PCR were more effective and sensitive than two other methods.